Prevalence of Under Nutrition and Its Risk Factors among Children below Two Years of Age in a Tertiary Health Centre in West Bengal - Das, Sukes; Mukherjee, Tanmoy; Chakraborty, Sajib; Das, Nivedita (National Journal of Community Medicine, 2022)
Background: Malnutrition in under five children is prevalent widely. It affects growth as well as development; also causes higher morbidity and mortality among children significantly. This public health problem is multi-factorial. Aim and Objectives: This study was conducted to estimate the prevalence of under nutrition and its risk factors among children up to 2 years of age attending a tertiary health care institution of Kolkata. Material and methods: This cross-sectional study was conducted among children aged 0 – 23 months, attending the Immunization clinic of CMSDH, Kolkata, during December, 2019 –January, 2020. Data were collected by interviewing the accompanying caregivers, anthropometric measurements of the study subjects and review of records. Results: Among 135 children studied, the prevalence of stunting was 14.1% (5.8% severely stunted), underweight was 9.7% (3.8% severely underweight), wasting was 18.5% (8.1% were SAM).Younger age group (0-6 months),boys and children having inappropriate feeding for age were at increased risk of under nutrition. Children having working mothers, birth spacing of <3 years, LBW and delayed initiation of breastfeeding (>1hour) were at higher risk of stunting and underweight. Incorrect age of introduction of complementary feeding had higher risk of wasting. Conclusion: Several risk factors for malnutrition were found which are amenable to prevention.